2022
DOI: 10.3390/molecules27238346
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Protopanaxatriol Saponins on Ulcerative Colitis in Mouse Based on UPLC-Q/TOF-MS Serum and Colon Metabolomics

Abstract: Ulcerative colitis (UC) is a chronic, nonspecific inflammation of the bowel that mainly affects the mucosa and submucosa of the rectum and colon. Ginsenosides are the main active ingredients in ginseng and show many therapeutic effects in anti-inflammatory diseases, cancer, and nervous system regulation. Protopanaxatriol saponin (PTS) is an important part of saponins, and there is no research on its pharmacological effects on colitis. In this study, a model of ulcerative colitis in mice was induced by having m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Studies have shown that berberine can play an anti-colitis role by regulating related metabolites through interaction with intestinal flora ( Jing et al, 2021 ). Importantly, Protopanaxatriol saponin can regulate a variety of differentiated metabolites and metabolic pathways ( Wu et al, 2022 ). Studies have also shown that spermidine can inhibit the activation of F4/80 macrophages and T cells, reduce the expression of pro-inflammatory cytokines and the phosphorylation of NF-κB and MAPK, and improve colitis through the above pathways ( Ma et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that berberine can play an anti-colitis role by regulating related metabolites through interaction with intestinal flora ( Jing et al, 2021 ). Importantly, Protopanaxatriol saponin can regulate a variety of differentiated metabolites and metabolic pathways ( Wu et al, 2022 ). Studies have also shown that spermidine can inhibit the activation of F4/80 macrophages and T cells, reduce the expression of pro-inflammatory cytokines and the phosphorylation of NF-κB and MAPK, and improve colitis through the above pathways ( Ma et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, A study has shown that berberine demonstrates an anti-inflammatory action and safeguards the integrity of the intestinal barrier through its interaction with the intestinal flora and regulation of associated metabolites ( Jing et al, 2021 ). Protopanaxatriol saponin has the potential to reduce the metabolic dysfunction through the restoration of abnormal changes in 29 metabolites and the regulation of eleven metabolic pathways ( Wu et al, 2022 ). Therefore, traditional Chinese medicine may play a biological function by regulating the relative abundance of intestinal microbial communities and thereby regulating the expression level of microbe-derived metabolites ( Gao et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, AA can be converted into prostaglandins enzyme-catalyzed by COX. During gouty inflammation, the first-line treatment strategy is COX inhibitors, such as unselective COX inhibitors (ibuprofen and aspirin) and COX-2-targeted agents (Etoricoxib) ( Wu et al, 2022 ; Burkett et al, 2023 ). The above inflammatory metabolites and mediators are worthy of attention in the management of gout.…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be attributed to the active components in astragalus such as astragalin and AS-IV that inhibit the proliferation and migration of cancer cells ( Li et al, 2020 ; Yang et al, 2021 ). Some bioactive components in ginseng , such as protopanaxatriol saponins, can also prevent the development of colorectal cancer in animals ( Majeed et al, 2018 ; Wu et al, 2022 ; Wang et al, 2023 ). A meta-analysis of 1,409 participants showed that astragalus -based medicines combined with chemotherapy may improve the tumor response rate and KPS and reduce incidences of nausea, vomiting, and neutropenia during the treatment of colorectal cancer ( Lin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%